Proceedings of the 2014 ACM International Joint Conference on Pervasive and Ubiquitous Computing: Adjunct Publication 2014
DOI: 10.1145/2638728.2638764
|View full text |Cite
|
Sign up to set email alerts
|

An immersive fire training system using kinect

Abstract: Lack of awareness of potential fire hazards is a leading factor of fire, especially when the child is alone. This paper presents a simulation training system to help children learn fire hazards knowledge and escape skills. The first part of this system is an application designed for theoretical study, which is featured by gesture interaction using Microsoft Kinect and large screen display environment. It includes three modules, namely animation, quizzes, and a 3D serious game. The second part is a simulated en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…There were many applications developed in the form of gaming to educate the children in teaching and learning [9], [10], [11]. Realizing the best ways to attract the children to stay focus during learning session by providing multimedia elements such as animation and audio [12], [13], [14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There were many applications developed in the form of gaming to educate the children in teaching and learning [9], [10], [11]. Realizing the best ways to attract the children to stay focus during learning session by providing multimedia elements such as animation and audio [12], [13], [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table III showed that the user requirements obtained after carrying out the experiment on the existing fire safety games. All the user requirements were focused on children's abilities, gaming elements and gaming factors [3], [6], [15], [19], [22], [25], [26].…”
Section: A Preliminary Study (Analysis Phase)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the immersive simulation training system helped the children to learn through gesture interaction using Microsoft Kinect and large screen display environment [13]. It showed that the improvements of escape skills of the children experiencing simulation training system.…”
Section: Introductionmentioning
confidence: 99%